A MPK3/6-WRKY33-ALD1-Pipecolic Acid Regulatory Loop Contributes to Systemic Acquired Resistance. Issue 10 (18th September 2018) - Wang, Yiming; Schuck, Stefan; Wu, Jingni; Yang, Ping; Döring, Anne-Christin; Zeier, Jürgen; Tsuda, Kenichi
Abstract : A positive feedback loop consisting of MPK3/6, WRKY33, ALD1, and pipecolic acid regulates local immune amplification contributing to systemic acquired resistance in Arabidopsis thaliana. Abstract: Plants induce systemic acquired resistance (SAR) upon localized exposure to pathogens. Pipecolic acid (Pip) production via AGD2-LIKE DEFENSE RESPONSE PROTEIN1 (ALD1) is key for SAR establishment. Here, we report a positive feedback loop important for SAR induction in Arabidopsis thaliana . We showed that local activation of the MAP kinases MPK3 and MPK6 is sufficient to trigger Pip production and mount SAR. Consistent with this, mutations in MPK3 or MPK6 led to compromised Pip accumulation upon inoculation with the bacterial pathogen Pseudomonas syringae pv tomato DC3000 ( Pto ) AvrRpt2, which triggers strong sustained MAPK activation. By contrast, P. syringae pv maculicola and Pto, which induce transient MAPK activation, trigger Pip biosynthesis and SAR independently of MPK3/6. ALD1 expression, Pip accumulation, and SAR were compromised in mutants defective in the MPK3/6-regulated transcription factor WRKY33. Chromatin immunoprecipitation showed that WRKY33 binds to the ALD1 promoter. We found that Pip triggers activation of MPK3 and MPK6 and that MAPK activation after Pto AvrRpt2 inoculation is compromised in wrky33 and ald1 mutants. Collectively, our results reveal a positive regulatory loop consisting of MPK3/MPK6, WRKY33, ALD1, and Pip in SAR induction and suggest the existence of distinct SAR activation pathways that converge at the level of Pip biosynthesis.